REINVIGORATE STUDENTS’ ENTHUSIASM FOR WRITING - Andi Hamzah Fansury (Publikasi dan UKI Press UKI Toraja., 2022)
Writing is a complex process that draws on: our knowledge of the topic, our ability to anticipate what readers will need, our ability to logically organize information, our skill at finding the right words, our ability to evaluate our efforts, and the perseverance to keep working. In this research, the writer expected to find out strategy to reinvigorate students’ enthusiasm in writing. Design of the research is qualitative research. The writer interviewed the English teacher and students to knowing some information from her/him about enthusiasm in writing. Successful navigation frequently results in reinvigorating students' enthusiasm for writing even if they struggle with learning disabilities. Three basic skills clusters are essential for efficiency in written expression: Use of letter form, spacing and lines, use of writing mechanics within the process of written expression and Organized use of content: clearly expressing basic ideas, with elaboration Successful writers integrate the following sub-skills: General Sub-skills, Mechanical Sub-skills and Contextual Sub-skills